2014
DOI: 10.1111/jgh.12481
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of steatohepatitis, fibrosis, and carcinogenesis in mice fed a methionine‐choline deficient diet by CCAAT/enhancer‐binding protein homologous protein deficiency

Abstract: CHOP deficiency attenuated apoptosis, inflammation, fibrosis, and tumorigenesis under fat-loading conditions, indicating that a therapeutic strategy targeting CHOP might be effective for fat-induced liver injury and protecting against promotion of carcinogenesis in patients with liver steatosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 45 publications
(103 reference statements)
2
46
0
Order By: Relevance
“…In addition, an excess of sucrose and trans-fat is supplemented in the formula of the MCD diet. These components exacerbated fat accumulation and hepatocellular damage of MCD diet-fed mice within 2-4 weeks [35, 55, 56]. Prolonged MCD feeding resulted in fibrosis (8 weeks) and the appearance of malignant neoplastic nodules in 3-6 months [55].…”
Section: Characteristics Of Currently Available Rodent Nash-hcc Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, an excess of sucrose and trans-fat is supplemented in the formula of the MCD diet. These components exacerbated fat accumulation and hepatocellular damage of MCD diet-fed mice within 2-4 weeks [35, 55, 56]. Prolonged MCD feeding resulted in fibrosis (8 weeks) and the appearance of malignant neoplastic nodules in 3-6 months [55].…”
Section: Characteristics Of Currently Available Rodent Nash-hcc Modelsmentioning
confidence: 99%
“…These components exacerbated fat accumulation and hepatocellular damage of MCD diet-fed mice within 2-4 weeks [35, 55, 56]. Prolonged MCD feeding resulted in fibrosis (8 weeks) and the appearance of malignant neoplastic nodules in 3-6 months [55]. The tumorigenicity may be potentiated by exposure to DEN during MCD diet feeding [55].…”
Section: Characteristics Of Currently Available Rodent Nash-hcc Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chop deletion protects mice from various hepatocyte-specific challenges, including bile duct ligation (Tamaki et al 2008), acetaminophen (Uzi et al 2013), alcohol feeding (Ji et al 2005), and diet-induced steatohepatitis (Rinella et al 2011;Toriguchi et al 2014). In contrast to the beneficial effect of Chop deficiency, Chop −/− mice fed a methionine-choline-deficient (MCD) diet display increased liver damage (Soon et al 2010), possibly explained by a net accumulation of activated macrophages due to decreased death in the absence of CHOP (Malhi et al 2013).…”
Section: Chop/ddit3/gadd153mentioning
confidence: 99%
“…In absence of CHOP, both cells and animals are protected against various pharmacological and physiological insults (Tabas and Ron, 2011). It has been shown that CHOP deficiency attenuates cholestasis-induced liver fibrosis and methionine-choline-deficient (MCD) diet-induced steatohepatitis, fibrosis, and carcinogenesis in mice (Tamaki et al, 2008; Toriguchi et al, 2013). In a murine model of intragastric ethanol feeding, CHOP null mice have remarkable absence of hepatocellular apoptosis, but no protection against alcohol-induced steatosis (Ji et al, 2005).…”
Section: Upr and Hepatic Lipid Homeostasismentioning
confidence: 99%